On Hausdorff-Young inequalities for quantum fourier transformations - Hudson, R. L. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
The classical Hausdorff-Young inequality for the Fourier transformation is generalized to various quantum contexts involving noncommutative L p -spaces based on translation-invariant traces.